Theoretical and Practical Determination of a Binary Mixture of AISI 316 Steel Powders to Increase Corrosion Resistance in Powder Metallurgical Parts (2022)
Powder metallurgical steels have lower corrosion resistance compared to wrought steels. Their behavior is simultaneously affected by interconnected porosity, pore morphology, interaction with sintering atmospheres, and metallurgical phenomena such as steel 'sensitization'. This work presents the theoretical methodology to calculate the optimum composition of the mixture and the conditions for a maximum packing of two sizes spheres (assuming a spherical shape factor) according to the development published by Brouwers for a system of binary mixtures. For the theoretical determination of the mixture, the results of density and porosity of a 316 powder metallurgical stainless steel made from prealloyed powders of two average granulometries (45μm and 150μm) are presented. The powders were combined in different proportions to define the appropriate quantities that allow the manufacture of steel with a low corrosion rate. The obtained results confirm that the theoretical calculation is a reliable alternative to formulate powder metallurgical alloys since good particle packing is achieved, which has a favorable effect on the characteristics of the finished product.